PREVALENCE OF KLEBSIELLA SPECIES ISOLATED FROM CLINICAL SAMPLES IN VIDARBHA REGION OF MAHARASHTRA STATE, INDIA - THOSAR M. G.; V. A. KAMBLE (International Journal of Pharma and Bio Sciences, 2014)
Klebsiella is a very frequent isolate in hospital environment and different Klebsiella species may vary with the type of infection they cause. This study was designed to determine the prevalence of different Klebsiella species in clinical samples collected from Amravati and Akola districts of Vidarbha region. A total of 1081 clinical samples were collected from different hospitals of Amravati and Akola district and Private pathology laboratories. The clinical samples viz; oral thrush, blood, urine, sputum, burn wound swab, cerebrospinal fluid and some miscellaneous samples were collected and cultured on MacConkey agar, Blood agar, UTI agar and MacConkey agar modified. A total of 437 (40.42%) clinical isolates of Klebsiella were isolated and identified at species level using various biochemical tests. Three different Klebsiella species were recovered among them, K. pneumoniae (385) was the commonest followed by K. oxytoca (51), while K. ozanae had only one isolate. Among different clinical samples, burn wound swabs (60.70%) showed highest prevalence of Klebsiella followed by sputum (45%), urine (42.86%), blood (34.40%), tracheal secretion (27.27%), oral thrush (32.4%), miscellaneous samples (20%) and CSF (2%). This study has provided the base line for generating data on the prevalence of different Klebsiella species in various clinical samples collected from Amravati and Akola district of Vidarbha region.